DISTINCT MANIFESTATIONS OF HIRSUTISM IN INDIGENOUS WOMEN (The Research of Medical Science Review, 2025)
This study was conducted to know the Indigenous symptoms of females with hirsutism in the perspectives of Pakistani culture. Many researchers revealed the changes in females with hirsutism which badly impacts their mental health as well as physical health. They face lots of social, emotional, psychological as well as physiological issues in daily life. Their impacts on daily life had detrimental effects in their lives. Female participants used to express the symptoms of hirsutism residing in Pakistan. The study method was quantitative research in nature. 300 female participants were a part of this research age range 18+ who are seeking laser treatments from laser/ aesthetic clinics. All females suffering from hirsutism are part of this research. The scale that was used to measure the hirsutism was Gallwey Scale 1 .These research findings are beneficial for future research.